Extent to which weight loss contributes to improving metabolic dysfunction-associated and metabolic and alcohol related/associated steatotic liver disease: a study on Japanese participants undergoing health checkups - Fukuda, Tatsuya; Okamoto, Takahiro; Fukaishi, Takahiro; Kawakami, Akio; Tanaka, Makoto; Yamada, Tetsuya; Monzen, Koshiro (Frontiers in Endocrinology, 2024)
Introduction The incidence of steatotic liver disease has increased in recent years. Thus, steatotic liver disease is a major public health issue in Japan. This study investigated the association between weight reduction and the remission of metabolic dysfunction-associated steatotic liver disease (MASLD)/Metabolic and alcohol related/associated liver disease (MetALD) in Japanese individuals undergoing health checkups. Methods This retrospective observational study included 8,707 Japanese patients with MASLD/MetALD who underwent health checkups from May 2015 to March 2023. The participants were monitored for its remission at their subsequent visit. MASLD was diagnosed on abdominal ultrasonography and based on the presence of at least one of five metabolic abnormalities. The impact of body mass index (BMI) reduction on MASLD/MetALD remission was assessed via logistic regression analysis and using receiver operating characteristic curves. Results Logistic regression analysis revealed that weight loss was significantly associated with MASLD/MetALD remission. Other factors including exercise habits and reduced alcohol consumption were significant predictors of MASLD/MetALD remission in the overall cohort and in male patients. The optimal BMI reduction cutoff values for MASLD/MetALD remission were 0.9 kg/m2 and 4.0% decrease in the overall cohort, 0.85 kg/m2 and 3.9% decrease in males, and 1.2 kg/m2 and 4.5% decrease in females. In participants with a BMI of 23 kg/m2, the cutoff values were 0.75 kg/m2 and 2.7% BMI reduction. Discussion Weight reduction plays an important role in both MASLD and MetALD remission among Japanese individuals. That is, targeting specific BMI reduction is effective. This underscores the importance of targeted weight management strategies in preventing and managing MASLD/MetALD in the Japanese population.